Devonian vertebrates from East Greenland: A review of faunal composition and distribution - Blom, H; Clack, J; Ahlberg, P; Friedman, M (2007)
The Devonian vertebrate faunas of East Greenland are reviewed and their distribution discussed for the first time in the light of the most recently published stratigraphical framework for the area. The predominantly Middle and Upper Devonian continental sediments have yielded representatives of most major groups of early fossil vertebrates, including heterostracans, placoderms, acanthodians, chondrichthyans, actinopterygians, lungfishes, porolepiforms, "osteolepiforms" and tetrapods, but to date, no single publication has treated them all in their stratigraphical context. We therefore attempt to place them into the most recent, formalised lithostratigraphy, providing improved resolution for their stratigraphical distribution, as a basis for comparing East Greenland with other Devonian faunal successions worldwide. The review highlights the fact that many problems of stratigraphical correlation and dating of the East Greenland Devonian deposits remain to be resolved by further fieldwork. Several assemblages ranging from Givetian to Famennian in age can be distinguished, that correspond to older superceded subdivisional nomenclature. A possible Frasnian fauna has been recognised for the first time, adding details to an otherwise poorly dated part of the succession. Typical Devonian taxa such as Holoptychius Agassiz, 1839 and Groenlandaspis Heintz, 1932 have apparently been recorded in an otherwise unique position above the Devonian-Carboniferous boundary in the upper part of the succession. New specimens of rare elements of the fauna including an unknown arthrodire placoderm, a putative chondrichthyan spine and a patch of possibly regurgitated acanthodian spines, are illustrated for the first time. © Publications Scientifiques du Muséum national d'Histoire naturelle.